Effectiveness of structured teaching programme regarding knowledge about uses of menstrual cup among nursing students - K. M., Ashwini; Kumar, Atul (International Journal of Research in Medical Sciences, 2024)
Background: Menstruation is a normal biological process experienced by millions of women around the world each month. Good menstrual hygiene practices can prevent infections among women. During menstruation women are using different sanitary products like reusable cloth pads, commercial sanitary pads, tampons, pads made from wool, reusable tampons, and menstrual cups. The menstrual cup was developed as an alternative of sanitary napkins and eco-friendly sanitary product but due to lack of awareness in India it’s uses are very limited. Methods: Quasi experimental one group pre-test and post-test research design was used in this research study. A total 201 nursing students of were selected by using purposive sampling technique. After the pretest structured teaching programme regarding knowledge of menstrual cap uses was implemented among nursing students and on 10th day of STP post-test was done by using the same tools. Results: During the pre-test researcher found that majority (81.59%) of nursing students had inadequate knowledge regarding menstrual cups uses. The mean knowledge score was significantly (p<0.05) increases from pre-test (7±3.06) to post-test (15±2.36) where mean difference was 8. Conclusions: The study results highlighted that the STP was highly effective in increase the knowledge among nursing students. Educational intervention programs must give importance in Professional Institutions, which will motivate female’s students to start practice of menstrual cups during menstruation. This is eco-friendly initiative.